PENGARUH PENGGUNAAN MODEL POLYA TERHADAP HASIL BELAJAR SOAL CERITA PECAHAN SISWA KELAS V SDN - Oktaviani, Wulan; Amini, Risda; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to know the effect  of the Polya model on student learning outcomes of fractional story problems  at 5th grade of Elementary School in III group  Ampek Angkek Subdistrict Agam District in the 2018/2019 school year. This research is a quantitative research with a type of quasi-experiment, design of Non-equivalent control group design. The population in this research is 5th grade in Elementary School III group in Ampek Angkek Subdistrict. The sample of this research is the 5th grade students of SDN 07 Sitapung consisting of two classes that is VA class is 20 students and VB class is 20 Students. Sampling was done with purpose sampling technique. The data announcement instrument used is a description test.  Based on the results of the research obtained tcount  ttable where tcount = 7.84  ttable = 1.72 means that Ha is accepted and Ho is rejected. This shows that the use of the Polya model has an effect on students learning outcomes of fractional  story of the of 5th grade  of the Elementary School III group in Ampek Angkek Subdistrict.Keyword : Polya model, learning outcomes, fractions